THE ROLE OF THE TEACHER IN THE ACQUISITION OF ARABIC AS A SECOND LANGUAGE IN BOARDING SCHOOLS - Jukri Adha Pohan; Zulfahmi Lubis (Jurnal Scientia, 2022)
Language is one of the major languages ​​in the world spoken by mankind. The function of language is as a communication tool that humans use to interact and relate to each other. In Indonesia, where the majority of the population is Muslim, Arabic is a second language. Meanwhile, the use of Arabic is minimal, especially for students. For most students, the acquisition and application of Arabic is underestimated and even considered unimportant, even though the main source for studying and studying the Al-Qur'an and Hadith is Arabic itself. especially for students who attend Islamic boarding schools, Arabic should have become their daily food in communicating.